2003
DOI: 10.1063/1.1632546
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal detection of local thermal effects during selective nanophotothermolysis

Abstract: Photothermal (PT) technique was applied to the detection of laser-induced local thermal effects around absorbing nanoparticles into cells. The experiments demonstrated the capability of this technique for studying the threshold and the dynamic of thermal events around even a single particle in a broad temperature range, including monitoring of microbubble dynamic. PT technique shows promise for optimizing cancer-cell killing by incorporation of gold nanoparticles into the cells (selective “nanophotothermolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
222
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(229 citation statements)
references
References 14 publications
6
222
0
1
Order By: Relevance
“…Noble metal nanoparticles provide remarkable opportunities in these applications due to their inherently low toxicity [31][32][33] and strongly enhanced optical properties associated with localized surface plasmon resonance [34][35][36]. The enhanced electromagnetic field surrounding such particles gives rise to large absorption, Rayleigh (Mie) scattering, raman scattering, and twophoton luminescence cross-sections, properties which have been utilized in photothermal cancer therapy [24][25][26][27][28][29][30] (PTT), surface enhanced Raman detection [37][38][39] (SERS), and diagnostic imaging [17][18][19][20] applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Noble metal nanoparticles provide remarkable opportunities in these applications due to their inherently low toxicity [31][32][33] and strongly enhanced optical properties associated with localized surface plasmon resonance [34][35][36]. The enhanced electromagnetic field surrounding such particles gives rise to large absorption, Rayleigh (Mie) scattering, raman scattering, and twophoton luminescence cross-sections, properties which have been utilized in photothermal cancer therapy [24][25][26][27][28][29][30] (PTT), surface enhanced Raman detection [37][38][39] (SERS), and diagnostic imaging [17][18][19][20] applications.…”
Section: Introductionmentioning
confidence: 99%
“…Selectivity is achieved by focused directional control or invasive [40][41][42] (fiber optic) positioning of the incident radiation, often pulsed [28][29][30] or continuous wave [24-28, 30, 48] (cw) laser, and is typically accompanied by preferential administration of photoactive molecules [60][61][62] or nano-scale particles. Photoexcitation of the latter two results in nonradiative relaxation by local heat transfer to the surrounding tumor environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, Zharov et al performed similar studies on the photothermal destruction of K562 cancer cells. They further detected the laser induced-bubbles and studied their dynamics during the treatment using a pump-probe photo thermal imaging technique (Zharov et al, 2003). O'Neal et al 2004 reported in vivo impressive results by showing selective photo-thermal ablation in mice using near infrared-absorbing NPs (O , Neal et al, 2004).…”
Section: Hyperthermia Treatmentmentioning
confidence: 99%
“…11,12 Like Raman spectroscopy, PhI is an all optical method, and it is based on the detection of refractive index variations that are induced by photothermal effect in the local environment of an absorbing nanoparticle. 13,14 A few variants of PhI exist, 13,15,16 and photothermal heterodyne imaging, which is the most sensitive scheme, 13,17 allows detecting several types of nano-objects at a single particle level. These include gold nanoparticles, even within a cell matrix and for membrane receptor dynamics studies in live cells, 18,19 molecules, quantum dots or single walled carbon nanotubes.…”
mentioning
confidence: 99%